Nanoparticles synthesised from Caesalpinia spinosa: assessment of the antifungal effects in protective systems - Gámez Espinosa, Erasmo Junior (2021)
Green chemistry is the preferred approach for the synthesis of metal and metal oxide nanoparticles due to its environmental friendliness, feasibility, and safety to human health when compared with other chemical or physical methods. Caesalpinia spinosa is a promising resource to be applied in the green synthesis of metallic nanoparticles due to the high amount of polyphenols. The aim of the present research was to obtain an antifungal coating functionalised with nanoparticles synthesised from C. spinosa tannin and aqueous solutions of metallic (silver and copper) salts to control biodeterioration of acrylic paints and bricks. Green synthesised NPs were characterised by UV-vis spectroscopy, transmission electron microscopy (TEM), Fourier transformed infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS). The silver nanoparticles with average size of 12 nm and obtained from a 500 ppm aqueous solution of C. spinosa tannin inhibited the growth of Aspergillus niger, Penicillium commune and Lasiodiplodia theobromae. These strains were previously isolated from a biodeteriorated facade. Functionalised coating obtained with silver nanoparticles synthesised from C. spinosa tannin is reported for the first time as antifungal protective system of acrylic paints and bricks.